Emotion Regulation of an Early Adult Woman Who Has Experienced Father-Perpetrated Violence - Sifabellla Bunga Priangga; Yasmin Rachmah Ramadhani; Dinar Saputra (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Violence perpetrated by fathers from childhood to early adulthood plays a major role in shaping an individual’s emotion regulation abilities. Emotion regulation is a crucial aspect of adaptive emotional functioning. This study aimed to explore in depth the processes and strategies of emotion regulation in an early adult woman who has experienced paternal violence.  A qualitative approach with a narrative research design was employed. Data were collected from one subject and two informants and analyzed using qualitative analysis, including data condensation, data display, and conclusion drawing. The findings indicate that experiences of family violence contribute to the development of maladaptive emotion regulation patterns, predominantly characterized by antecedent-focused strategies such as avoidance, distraction, and rumination, while also involving response-focused strategies, including expressive suppression and emotion expression. Trauma can disrupt emotion regulation flexibility, prompting individuals to adopt defensive patterns and reducing their capacity to cope with emotional stress adaptively. These findings highlight the complexity of emotion regulation shaped by traumatic experiences and provide a contextual understanding among early adult women who have experienced paternal violence. Keywords: childhood trauma, emotion regulation, early adult women, paternal abuse